Selling ways of local traditional products and their influence in sustainable rural development - Nela Dragomir; Vili Dragomir (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In Romania, some traditional foods present risk of disappearing due to altered lifestyle. In this paper we address the concept of sustainable which referring to time, a long time. Sustainable process must be converted to sustainable human development, oriented mainly towards quality of life and environment in special for obtain traditional products local, by creating ethical relations between consumers and producers, in an era of globalization, industrialization and products standardized. The conservation and valorization of local/traditional products could increase the adoption of more sustainable agricultural systems together with the adoption of practices more restrictive regarding of environment and the natural habitats. So, biodiversity in the food systems is absolutely crucial for both a sustainable food production and food security. Diets based on different food species promote health by addressing the problem of micronutrient and vitamin deficiencies. Therefore, it seems that the transition towards sustainable forms of agriculture cannot be deferred further.
Keywords: 330; sustainable; local; trade; tradition